OPTIMALISASI PELAYANAN DISTRIBUSI AIR BERSIH UNTUK MENINGKATKAN PENDAPATAN PDAM KOTA MAGELANG - Luk, Luk Luk (Jurnal Analisis Bisnis Ekonomi, 2004)
The economics crisis in Indonesia brings negative impact to the PDAM of Magelang Municipality in the decreasing profit of the firm. This was caused by the increasing amount of operational and maintenance and operational cot, meanwhile the income was relatively constant. The maintenance increased as an impact pipes prices and equipments. Higher electricity cost also increased the operational cost. PDAM as district firm as a full responbility to give public services operationally contrary o that the firm had to be able to obtain fair profit. In other hand, fair profit would support the firm in developing services through the impovement of water distribution network in areas with no clean water access. Potential alternative as a solution in this condition revealed in the optimalization of clean water distribution capacity. PDAM had potential midle capacity of 8.13 l/s. The strategy to implement the alternative was to consider land use plan, structure of distribution network and target market, which were explicitly determined the development target to give optimum income. The targets areas to support the alternative were Jurangombo and Tidar district. These area mainly cover the land use of industrial and commercial activities, so the assumptions was the ability to pay in this population of settlement areas. The development of Jurangombo and Tidar district contribute Rp. 1,205,278,228.00 and obtained 7.861l/s of water distribution capacity. Total invesment of Jurangombo and Tidar development was Rp. 985,000,000.00 and colud beliable financially. The pay pack period of time were estimated 1 year 1 month, with the probability index of 1.063 ; internal rate of return with the value of 18.67% and the net present value with the positive walue of Rp. 62,121,471.82. The development distribution capacity of Jurangombo and Tidar district were explicitly feasible. In consideration, the development shouls be immedialety implementes to overcome the financial problems and realized social responsibility.